1977
DOI: 10.1073/pnas.74.8.3498
|View full text |Cite
|
Sign up to set email alerts
|

Gene regulation in Drosophila mulleri, D. arizonensis , and their hybrids: The nucleolar organizer

Abstract: Typically, Dwsophila have nucleolar organizer regions (NORs) confined to the sex chromosomes. Salivary gland cells of hybrids between Drosophila mulleri females and D. arizonensis males exhibit features in nucleolar organizer regulation that differentiate the species on one hand, and which show an interplay between the X and the microchromosome on the other hand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

1978
1978
2000
2000

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…Such a change is well developed in inter-species hybrids: C. plumosus x C. vancouveri and C. plumosus x C. balatonicus. We suppose that the mechanisms acting in hybrids of D. mafleri × D. arizonensis (Bicudo & Richardson, 1977) are in effect here as well. In the initial form ofD.…”
Section: Discussionmentioning
confidence: 99%
“…Such a change is well developed in inter-species hybrids: C. plumosus x C. vancouveri and C. plumosus x C. balatonicus. We suppose that the mechanisms acting in hybrids of D. mafleri × D. arizonensis (Bicudo & Richardson, 1977) are in effect here as well. In the initial form ofD.…”
Section: Discussionmentioning
confidence: 99%
“…Such a distribution of the NORs has not yet been reported in Drosophila. In other Drosophila species, where the NORs have been localized, they are restricted either to the X and Y chromosomes ( D. melanogaster, D. simulans, D. hyde# Spear, 1974;Hennig et al, 1975;Mohan, 1977), to the X chromosomes (D. virilis, D. mulleri, D. arizonensis, " Endow & Gall, 1975;Bicudo & Richardson, 1977) or to the microchromosomes only (D. tumiditarsus, " Sinibaldi & Cummings, 1981). Our findings in the two Drosophila nasuta races are the second cases where the X chromosomes are devoid of NORs.…”
Section: Discussionmentioning
confidence: 99%
“…In related studies they suggested that the regulation of the nucleolar organizer region could be related to interspecific differences in developmental rates and, possibly, to hybrid inviability (Bicudo and Richardson, 1978) . Since developmental rates, mating behavior and viability all may be affected by a single change in the location of a block of heterochromatin, repositioning heterochromatin in the genome may have far greater effect on the phenotypic diversity of organisms than would, say, a mutation in a structural gene.…”
Section: Crassijemur)mentioning
confidence: 99%
“…Recently, Bicudo and Richardson (1977) have reported interchromosomal effects on gene regulation (nucleolar organizer activity) between the microchromosomes and the X, which extends the realm of the potential effects on genetic regulation to a higher order effect, beyond the single chromosome. In related studies they suggested that the regulation of the nucleolar organizer region could be related to interspecific differences in developmental rates and, possibly, to hybrid inviability (Bicudo and Richardson, 1978) .…”
Section: Crassijemur)mentioning
confidence: 99%
See 1 more Smart Citation